MIGRATION AND REMITTANCES IN KERALA - J. Vineesh Prakash; D.K. Nauriyal and Noushad A.P
This paper examines the trends and patterns of international migration in Kerala, and assesses the impact of remittances on the state’s economy. It uses annual data of NSDP of Kerala at current prices as a proxy for its economic growth and remittances estimated by the various reports of Kerala Migration Surveys and Kerala Development Reports from 1980-81 to 2013-14. ARDL bound testing methodology has been applied to test the existence of long run relations between economic growth and remittances, which provides a more robust results when sample size is small. Akaike info criterion has also been used to determine the lag length of the ARDL model. The result of the bound test confirms the existences of long run relationship between remittances and economic growth. The results further reveals that remittances have laggard influence on economic growth in the short run. Since, a major portion of remittances is used in building of houses and to meet the household requirements, it led to the growth of a host of industries viz., construction, trade, banking and insurance, transport etc. Traditionally, emigrations from the state are mostly unskilled and semi-skilled in nature, but a recent increase at a declining rate, coupled with steady rise in remittances indicates a paradigm shift from unskilled labour migration to skilled labour migration from the state.